Translation Equivalence of Plenger in Instagram Captions - Raden Roro Shinta Felisia (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Since last year, plenger has become a common expression on social media, especially among Indonesian users. According to a post by Balaibahasaprovinsintb, plenger refers to someone who behaves strangely, carelessly, foolishly, or absent-mindedly. Although plenger is generally described as having a negative connotation, it can also refer to a positive condition, such as someone who is fully devoted to their hobbies, interests, or areas of expertise (Popbela.com). This study describes the English translations of plenger. Five instances of plenger (71%) are translated into English, while two instances (29%) were retained as plenger in the translation. The types of translation equivalence identified for plenger are pragmatic equivalence (57%), formal equivalence (29%), and denotative equivalence (14%).